2010
DOI: 10.1371/journal.pone.0008575
|View full text |Cite
|
Sign up to set email alerts
|

Mild Hypoxia Enhances Proliferation and Multipotency of Human Neural Stem Cells

Abstract: BackgroundNeural stem cells (NSCs) represent an optimal tool for studies and therapy of neurodegenerative diseases. We recently established a v-myc immortalized human NSC (IhNSC) line, which retains stem properties comparable to parental cells. Oxygen concentration is one of the most crucial environmental conditions for cell proliferation and differentiation both in vitro and in vivo. In the central nervous system, physiological concentrations of oxygen range from 0.55 to 8% oxygen. In particular, in the in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
144
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(165 citation statements)
references
References 44 publications
20
144
0
1
Order By: Relevance
“…Physiological microenvironments play a crucial role in maintenance of stem cell properties, and the oxygen concentration is an important component of the stem cell niche (Peerani and Zandstra 2010;Santilli et al 2010). In the present study, hypoxia provokes MSCs proliferation, and increases ALP activity and production of both Col I/III.…”
Section: Discussionsupporting
confidence: 50%
“…Physiological microenvironments play a crucial role in maintenance of stem cell properties, and the oxygen concentration is an important component of the stem cell niche (Peerani and Zandstra 2010;Santilli et al 2010). In the present study, hypoxia provokes MSCs proliferation, and increases ALP activity and production of both Col I/III.…”
Section: Discussionsupporting
confidence: 50%
“…For example, hematopoietic stem cells are maintained in hypoxic niches in bone marrow (Parmar et al, 2007). Interestingly, hypoxia also prevents the differentiation of neural stem cells and promotes the maintenance of self-renewal potential of embryonic stem (ES) cells (Studer et al, 2000;Marrison et al, 2000;Ezashi et al, 2005;Santilli et al, 2010). In addition, restricted oxygen concentrations have been shown to enhance the production of induced pluripotent stem cells (iPSC) (Yoshida et al, 2009).…”
Section: Hypoxic Responses In Glioblastoma Stem Cellsmentioning
confidence: 99%
“…In addition, near-physiological oxygen tensions (5-6%) improve the efficiency of induced pluripotent stem cell generation (79). Several studies on in vitro differentiation of neural stem cells have shown that low oxygen levels promote proliferation, survival and multipotency as compared to normoxic oxygen levels (80)(81)(82)(83)(84)(85)(86). Hematopoietic stem cells (HSCs) in the bone marrow have been proposed to exist in a low oxygen milieu (87,88).…”
Section: Hypoxia and The Stem Cell Phenotypementioning
confidence: 99%